Nishga Perceptions of Their First Resident Missionary, the Reverend R. R. A. Doolan (1864-1867) - Patterson II, E. Palmer (Anthropologica, 2022)
This essay examines the Nishga view of their first resident missionary, the Reverend R.R.A. Doolan, whom they had taken the initiative in inviting to their villages. Through Doolan's letters and journals, over a three year period, a picture emerges of Nishga responses and attitudes to him. The comments and conversations of many individuals have been preserved. Most of the people regarded him as a useful adjunct to their community, although their views of his value to them did not correspond in every particular to his own notions of his purposes among them.